1995
DOI: 10.1002/art.1780380211
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of sexual abuse in women with fibromyalgia

Abstract: Objective. To determine the prevalence of sexual abuse in women diagnosed as having fibromyalgia (FM) compared with controls.Methods. A self-administered questionnaire designed to obtain information regarding demographics, health care utilization, and history of sexual and physical abuse was completed by 40 women with FM and by 42 women who had no evidence of connective tissue disease or other major medical condition.Results. Women with FM reported more physical symptoms and were significantly different on mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
53
3
4

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 119 publications
(64 citation statements)
references
References 9 publications
4
53
3
4
Order By: Relevance
“…Error in classification would underestimate true differences between those with or without self-reported abuse, and could increase the inaccuracy of regression model estimates. However, the self-reported abuse prevalence among FM patients in our sample is similar to that reported in other FM tertiary care populations (Taylor et al, 1995;Goldberg et al, 1999;Carpenter et al, 2004), and the validity of the brief selfreport measure used in the study is supported by the lower CSF CRF levels found among those reporting abuse, which is consistent with the known biological affects of early life stress (Carpenter et al, 2004;Heim et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Error in classification would underestimate true differences between those with or without self-reported abuse, and could increase the inaccuracy of regression model estimates. However, the self-reported abuse prevalence among FM patients in our sample is similar to that reported in other FM tertiary care populations (Taylor et al, 1995;Goldberg et al, 1999;Carpenter et al, 2004), and the validity of the brief selfreport measure used in the study is supported by the lower CSF CRF levels found among those reporting abuse, which is consistent with the known biological affects of early life stress (Carpenter et al, 2004;Heim et al, 2004).…”
Section: Discussionsupporting
confidence: 86%
“…This finding is consistent with that of Carpenter et al (2004), who found that perceived life stress during the preteen years was associated with decreased CSF CRF. The influence of selfreported childhood abuse has only recently been assessed in studies of stress axis function in FM (McLean et al, 2005b;Weissbecker et al, 2005), despite the fact that FM patients are often recruited for research studies from tertiary care clinic populations, where the prevalence of self-reported abuse is often 50% or more (Taylor et al, 1995;Goldberg et al, 1999;Carpenter et al, 2004). These recent studies describe relatively low cortisol levels in FM patients reporting a history of childhood abuse, and relatively high levels in those not reporting a history (McLean et al, 2005b;Weissbecker et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Sexual and physical abuse was assessed with an interview previously used in the National Population Survey of Canada and in recent studies of FMS patient groups (13,14,18). Patients and nonpatients were classified as either abused or nonabused based on their responses to 7 questions regarding abuse during childhood or adulthood.…”
Section: Methodsmentioning
confidence: 99%
“…This relationship was evaluated after controlling for demographic factors and a history of sexual or physical abuse, both of which are associated with increased health care usage and frequently occur among patients with FMS (11)(12)(13)(14). Three central issues were then examined regarding relationships between perceived physical and emotional trauma and several outcomes in patients with FMS.…”
mentioning
confidence: 99%
“…Other authors found a high prevalence (> 30%) of sexual and physical abuse in women with FM and reported higher rates of abuse in these patients as compared with a group of women without FM [45][46][47]. However, still other authors questioned the association between sexual abuse and FM onset [48][49][50].…”
Section: Discussionmentioning
confidence: 99%